Aortic Hybrid Sutureless Anastomosis on Porcelain Aorta. (April 2015) - Bonvini, Stefano; Zavatta, Marco; Grego, Franco; Piazza, Michele
Purpose: To describe a hybrid sutureless anastomosis technique between a prosthetic graft, an endograft, and a circumferentially calcified infrarenal aorta.Technique: The technique is demonstrated in a 65-year-old man with flush distal aortoiliac occlusion and patent infrarenal porcelain aorta (IPA). After laparotomy, the IPA was occluded below the renal arteries by inflating an aortic balloon introduced via an axillary access. The IPA was transected in its distal part and aortic thrombectomy performed. A Zenith iliac extension was modified on a back table by cutting the terminal tip; the device was then was inserted and deployed into the IPA in a standard fashion and the sheath removed. A Dacron bifurcated graft was sutured in an end-to-end anastomosis to the endograft and terminal aorta. The 12-month computed tomography scan showed patency of the graft.Conclusions: This sutureless anastomosis technique seems safe and feasible and represents a valid alternative to standard surgical approaches in cases of heavy and circumferentially calcified infrarenal aorta.